Impacts of free-roaming dogs on spatiotemporal niches of native carnivores in Taiwan - Hsin-Cheng Ho; Tzung-Su Ding; Hsiao-Wei Yuan; Jo-Szu Tsai; Guo-Jing Weng; Yu-Hsiu Lin; Hsiang Ling Chen; Yu-Bo Huang; Shih-Ching Yen (Global Ecology and Conservation)
Among animals of the same trophic level, niche partitioning often occurs to facilitate coexistence. However, when a new common predator appears, they may adjust their activity temporally and spatially to avoid the predator. Such changes may increase their niche overlap with each other. Dogs (Canis familiaris) are invasive carnivores that are distributed widely, and they pose serious threats to native mammals in Taiwan. We hypothesize that free-roaming dogs dominate spatial and temporal resources, which forces native mesocarnivores to adjust their realized niches to avoid dogs. We predict that threats from free-roaming dogs result in (1) the activity levels of native carnivores being correlated negatively with those of dogs, (2) native carnivores undergoing spatial or temporal avoidance in response to the presence of dogs, and (3) increased spatial or temporal niche overlap among native carnivores. This study covers four mesocarnivores in Taiwan: the masked palm civet (Paguma larvata), ferret badger (Melogale moschata), small Indian civet (Viverricula indica), and crab-eating mongoose (Herpestes urva). With data from 1270 camera traps, we used relative activity index (RAI), occupancy models, and kernel density estimation to analyze changes in abundance and spatiotemporal niche overlaps. A significant negative correlation was found between dog RAI and those of ferret badgers (p < 0.001) and crab-eating mongooses (p < 0.05). The ferret badgers also avoided dogs spatially (Species Interaction Factor, SIF < 1). However, crab-eating mongooses co-occurred with dogs spatially (SIF > 1), possibly due to their strong dependence on specific environments (i.e., forests around freshwater environments). We did not detect changes in spatiotemporal niche overlap among native carnivores. Variations in niche overlap may need to be observed at finer scales or across other dimensions. This study demonstrates the impact of free-roaming dogs on ferret badgers and crab-eating mongoose, which highlights the importance of conserving riparian environments from the threat of dogs. Future research that integrates other niche dimensions is necessary to better understand the impact of dogs.